2000
DOI: 10.1006/aama.2000.0699
|View full text |Cite
|
Sign up to set email alerts
|

On Quantum Algorithms for Noncommutative Hidden Subgroups

Abstract: Quantum algorithms for factoring and finding discrete logarithms have previously been generalized to finding hidden subgroups of finite Abelian groups. This paper explores the possibility of extending this general viewpoint to finding hidden subgroups of noncommutative groups. We present a quantum algorithm for the special case of dihedral groups which determines the hidden subgroup in a linear number of calls to the input function. We also explore the difficulties of developing an algorithm to process the dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
96
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(97 citation statements)
references
References 15 publications
1
96
0
Order By: Relevance
“…Ettinger, Høyer and Knill [5] show that for any group there exists a sequence of polynomially many queries, from which, with exponentially many measurements, we can reconstruct the hidden subgroup. For the special case of the dihedral group Dn Ettinger and Høyer [4] showed how to obtain sufficient statistical information about the hidden subgroup using polynomially many queries and polynomially many measurements; leaving open the question of whether there is an efficient reconstruction algorithm using that data. The dihedral group is interesting because by some measures it is not far from abelian, for instance none of its irreps have dimension greater than 2; on the other hand by our measure defined above, it is highly nonabelian, since |M (Dn)| ≤ 2.…”
Section: Overviewmentioning
confidence: 99%
“…Ettinger, Høyer and Knill [5] show that for any group there exists a sequence of polynomially many queries, from which, with exponentially many measurements, we can reconstruct the hidden subgroup. For the special case of the dihedral group Dn Ettinger and Høyer [4] showed how to obtain sufficient statistical information about the hidden subgroup using polynomially many queries and polynomially many measurements; leaving open the question of whether there is an efficient reconstruction algorithm using that data. The dihedral group is interesting because by some measures it is not far from abelian, for instance none of its irreps have dimension greater than 2; on the other hand by our measure defined above, it is highly nonabelian, since |M (Dn)| ≤ 2.…”
Section: Overviewmentioning
confidence: 99%
“…Although the dihedral group has a much simpler structure than the symmetric group, no solution to the HSP on the dihedral group is known. Ettinger and Høyer [7] showed that one can obtain sufficient statistical information about the hidden subgroup with only a polynomial number of queries. However, the question of finding an efficient algorithm that uses this information to solve the HSP is still open.…”
Section: Introductionmentioning
confidence: 99%
“…(8,17−19) An important unsolved problem in quantum computation theory is the hidden subgroup problem. (5)(6)(7)(11)(12)(13)22) Let H be a subgroup of a finite group G and let X be a nonempty set. A function f : G → X separates cosets of H if for every g 1 , g 2 ∈ G, f (g 1 ) = f (g 2 ) if and only if Hg 1 = Hg 2 .…”
Section: Introductionmentioning
confidence: 99%